Mast Cell Coupling to the Kallikrein–Kinin System Fuels Intracardiac Parasitism and Worsens Heart Pathology in Experimental Chagas Disease - Nascimento, Clarissa R.; Andrade, Daniele; Carvalho-Pinto, Carla Eponina; Serra, Rafaela Rangel; Vellasco, Lucas; Brasil, Guilherme; Ramos-Junior, Erivan Schnaider; da Mota, Julia Barbalho; Almeida, Larissa Nogueira; Andrade, Marcus V.; Correia Soeiro, Maria de Nazaré; Juliano, Luiz; et al. (Frontiers in Immunology, 2017)
During the course of Chagas disease, infectious forms of Trypanosoma cruzi are occasionally liberated from parasitized heart cells. Studies performed with tissue culture trypomastigotes (TCT, Dm28c strain) demonstrated that these parasites evoke neutrophil/CXCR2-dependent microvascular leakage by activating innate sentinel cells via Toll-like receptor 2 (TLR2). Upon plasma extravasation, proteolytically derived kinins and C5a stimulate immunoprotective Th1 responses via cross-talk between bradykinin B2 receptors (B2R) and C5aR. Awareness that TCTs invade cardiovascular cells in vitro via interdependent activation of B2R and endothelin receptors (ETAR/ETBR) led us to hypothesize that T. cruzi might reciprocally benefit from the formation of infection-associated edema via activation of kallikrein-kinin system (KKS). Using intravital microscopy, here we first examined the functional interplay between mast cells (MC) and the KKS by topically exposing the hamster cheek pouch (HCP) tissues to dextran sulfate (DXS), a potent “contact” activator of the KKS. Surprisingly, although DXS was inert for at least 30 min, a subtle MC-driven leakage resulted in factor XII (FXII)-dependent activation of the KKS, which then amplified inflammation via generation of bradykinin (BK). Guided by this mechanistic insight, we next exposed TCTs to "leaky" HCP- forged by low dose histamine application- and found that the proinflammatory phenotype of TCTs was boosted by BK generated via the MC/KKS pathway. Measurements of footpad edema in MC-deficient mice linked TCT-evoked inflammation to MC degranulation (upstream) and FXII-mediated generation of BK (downstream). We then inoculated TCTs intracardiacally in mice and found a striking decrease of parasite DNA (qPCR; 3 d p.i.) in the heart of MC-deficient mutant mice. Moreover, the intracardiac parasite load was significantly reduced in WT mice pretreated with (i) cromoglycate (MC stabilizer) (ii) infestin-4, a specific inhibitor of FXIIa (iii) HOE-140 (specific antagonist of B2R) and (iv) bosentan, a non-selective antagonist of ETAR/ETBR. Notably, histopathology of heart tissues from mice pretreated with these G protein-coupled receptor (GPCRs) blockers revealed that myocarditis and heart fibrosis (30 d.p.i.) was markedly and redundantly attenuated. Collectively, our study suggests that inflammatory edema propagated via activation of the MC/KKS pathway fuels intracardiac parasitism by generating infection-stimulatory peptides (BK and endothelins) in the edematous heart tissues.